Pengaruh Perbedaan Konsentrasi Perendaman Larutan Na Sitrat Terhadap Perubahan Berat Setelah Pemasakan Dan Daya Terima Nasi Jagung - Dewati, Iput; , Fitriana Mustikaningrum, S.Gz., M.Sc; , Pramudya Kurnia, STP., M.Agr (2017)
Background: Corn is a commodity that needs to be considered, in addition to easy to get corn also has a big opportunity to be developed as an alternative staple food because it has particularly primary nutrient content. In the manufacturing process using immersion phase with Na Citrate solution that can disrupt and outlines the structure of proteins and to accelerate the ripening time. The solution used can affect weight change after ripening corn rice and panelists acceptance of the product. Objective: The aim of this study to analyze the effects of different concentrations of Na Citrate solution in the manufacture of corn rice to changes in weight and acceptance as well as the values of Islamic materials used are allowed in the study. Methods: This study is a research and experiment with Annova test using 25 panelists to test acceptance on corn rice. A test of acceptability with the color, aroma, flavor, texture and overall liking and changes in weight after cooking using the method of calculating the change in the weight of the corn rice Hermawaty 2007 Results: The results showed that the acceptance panelists to color rice maize by 0.5% most preferably 68%, of the aroma of rice maize by 1.0% most preferably 12%, of the taste of rice maize by 1.0% most preferably 32% , the texture of the rice maize by 1.0% most preferably by 100% as well as the overall favorite corn rice, equal to 1.0% most preferably 96 Conclusion: There is the effect of immersion Na Citrate solution to the acceptability of rice corn. Based on the color, aroma, flavor, texture and overall liking. Suggestions: Taking into account the change in weight after cooking and acceptance, suggested the use of a 0.5% solution of Na Citrate